DIETARY INFLUENCES ON ACNE VULGARIS: INSIGHTS FROM KEY NUTRITIONAL MODELS - Wiktor Kubik; Bartłomiej Czarnecki; Jan Nowak; Illia Koval; Bartosz Zwoliński; Kacper Sukiennicki; Wirginia Bertman; Natalia Kołdej; Zuzanna Kępczyńska; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Acne vulgaris (AV) is a prevalent inflammatory dermatosis with substantial psychosocial burden. Diet can modulate AV via insulin/IGF-1/mTORC1 signalling, inflammation, lipid metabolism, and oxidative stress, yet many patients self-modify diet without structured guidance. Aim: To synthesise how key dietary patterns and components influence acne biology and clinical severity, and to distil pragmatic counselling points. Materials and Methods: Structured analysis of PubMed (2020–2025) using “acne” AND “diet.” A broad range of study types was considered. Priority was given to evidence on AV in populations without comorbid conditions (e.g., PCOS). The synthesis focused on dietary patterns and specific food groups; studies centred primarily on vitamins, supplements, or the microbiome were not the focus. Results: Glycaemic load (GL) is a key modifiable driver. Low-GL patterns show the strongest clinical signal and are directly actionable. Higher intake of sugary drinks, sweet snacks, and refined grains aligns with greater acne burden, consistent with insulin–mTORC1 activation. Mediterranean-style eating associates with lower severity and favourable metabolic markers. Plant-forward diets appear beneficial when emphasising whole-food, low-GL choices; veganism per se and routine gluten-free eating lack support without specific indications. Dark chocolate may aggravate lesions in some individuals through non-glycaemic mechanisms. Dairy may warrant cautious, personalised reduction while maintaining micronutrient adequacy. Shifting fat quality toward MUFA/omega-3s and away from saturated fat aligns with lower inflammatory burden. Conclusions: Dietary counselling should complement dermatological therapy. Low-GL and Mediterranean-style patterns show the most consistent associations with reduced acne burden; rigorous trials of whole-diet interventions remain needed.